Application of Strategic Management Information System (SMIS) in the Ministry of Interior, UAE: Issues and Challenges - Yaser Alraei, Alnekhaira Buti Alshamsi; Joseph, Adaikalam; Asif, Mahbub Karim; Hock, Oo Yu (2020)
The purpose of this paper is to present and describe SMIS implementation challenges or problems as well as identifying the key issues to achieve successful implementation. Moreover, this research seeks to explain the implementation effects and consequences which impact the organization and its processes. We investigate the key challenges faced for implementing SMIS in the Ministry of Interior, UAE. Quantitative methodology used and structured questionnaire was imployed.150 respondents were participated in this study and data was analyzed by using SPSS V.19. The findings show that budgetary, infrastructural and human resource capabilities have significant impact on the performance of SMIS. It is recommended to invest in technology development and taking initiatives to enhance skill of employee. Increase awareness at every level of the management, from the grass root level should be practiced as to make all aware that such a strategic management information system exists in the ministry of interior. Better regulatory observation needed to be adhered to monitor the information system and adhere to compliance issues. Training facilities by both in house and external trainers required on the latest software and application of strategic management information system.